Assessing Executive Function in Adolescence: A Scoping Review of Existing Measures and Their Psychometric Robustness - Nyongesa, Moses K.; Ssewanyana, Derrick; Mutua, Agnes M.; Chongwo, Esther; Scerif, Gaia; Newton, Charles R. J. C.; Abubakar, Amina (Frontiers in Psychology, 2019)
Background: There is much research examining adolescents’ executive function (EF) but there is little information about tools that measure EF, in particular preference of use, their reliability and validity. This information is important as to help both researchers and practitioners select the most relevant and reliable measure of EF to use with adolescents in their context. Aims: We conducted a scoping review to: a) identify the measures of EF that have been used in studies conducted among adolescents in the past 15 years; b) identify the most frequently used measures of EF; and c) establish the psychometric robustness of existing EF measures used with adolescents. Methods: We searched three bibliographic databases (PsycINFO, Ovid Medline and Web of Science) using key terms “Adolescents”, “Executive Functions”, and “measures”. The search covered research articles published between 1st January 2002 to 31st July 2017. Results: We identified a total of 339 individual measures of EF from 705 eligible studies. The vast majority of these studies (95%) were conducted in high income countries. Of the identified measures, 10 were the most used frequently, with a cumulative percent frequency accounting for nearly half (44%) the frequency of usage of all reported measures of EF. These are: Digit Span (count=160), Trail Making Test (count=158), Behaviour Rating Inventory of Executive Function (count=148), Wisconsin Card Sorting Test (count=140), Verbal Fluency Tasks (count=88), Stroop Colour-Word Test (count=78), Classical Stroop Task (count=63), Colour-Word Interference Test from Delis-Kaplan battery (count=62), Rey-Osterrieth Complex Figure Test (count=62), and Original Continuous Performance Test (count=58). In terms of paradigms, tasks from Span (count=235), Stroop (count=216), Trails (count=171), Card sorting (count=166), Continuous performance (count=99), and Tower (count=94) paradigms were frequently used. Only 48 studies out of the included 705 reported the reliability and/or validity of measures of EF used with adolescents, but limited to studies in high income countries. Conclusion: We conclude that there is a wide array of measures for assessing EF among adolescents. Ten of these measures are frequently used. However, the evidence of psychometric robustness of measures of EF used with adolescents remains limited to support the validity of their usage across different contexts.